"Into the great wide open": Integrating open science and research into information literacy teaching at Tampere University Library - Miettinen, Mervi (Septentrio Conference Series, 2020)
Open science and research is no longer relevant just for people pursuing an academic career. Instead, it is something that all students entering the university should be increasingly familiar with as they proceed with their studies. Tampere University Library has actively integrated open science into its information literacy teaching, beginning from the first-year orientation studies and continuing throughthe Bachelor’s and Master’s thesis seminars. Following the guidelines provided by the idea of cumulative learning (Maton 2009), the IL teaching at Tampere University Library aims at connecting new knowledge with existing knowledge, effectively building on the students’ previous IL studies throughout their degree. In addition, the ACRL Framework for Information Literacy (2015) acts as a roadmap for developing IL teaching at Tampere University Library: the Library’s entire teaching team has gathered in workshops and together produced a view of the frames that best suits the University’s students. The frames are awork-in-progress, and the teaching team will continue to work on better adapting the frames. One of the results is the way in which the frames and the threshold concepts within determine the depth inwhich issues such as open science and research are taught at different levels (cf. Sipilä, Miettinen &Tevaniemi, 2019). In order to ensure student engagement, concepts like open science are presented at each level in a way that is relevant to the students’ current studies, beginning with the concept itself and later advancing towards viewing the students as both users and creators of open science. This presentation will highlight some of the current ways in which open science and research is integrated into the information literacy curriculum at Tampere University Library, and how the ACRL framework can act as a way for library teaching staff to comprehend and develop IL teaching in highereducation.